On the Cusp of Sacred Anarchy: John Caputo’s Divine Weakness Witnessed in the Praxis of Dorothy Day’s Catholic Worker - Tomszak, Martin (Political theology, 2022)
In the wake of post-structuralism, as theologians, we cannot limit ourselves to the realm of negation and the hopelessness of deconstruction without the horizon of building anew. There must be a concise effort on the part of theology, through the lens of anatheistic theology specifically, to push past the boundaries of admitting weakness and rejecting sovereignty as well as to avoid the relegation of such discussions to the realm of theory. The following article will examine the ways in which such steps might be taken through a comparison of John Caputo’s reflection on Divine Weakness and Sacred Anarchy as it relates to the Catholic Worker movement begun by Dorothy Day. The intersections between the theopoetic outlining of concepts within Caputo’s canon and the practical actions of the Catholic Worker movement and its radical lay apostolate highlights the potential that such a marriage of theory and praxis may have as we firmly move into a new millennium.